Fe3O4/PPy-Coated Superhydrophilic Polymer Porous Foam A Double Layered Photothermal Material with a Synergistic Light-to-Thermal Conversion Effect toward Desalination - He, Jingxian (Langmuir : the ACS journal of surfaces and colloids, 2021)
Solar steam generation has been considered as one of the most promising strategies for production of fresh water using renewable solar energy. Herein, we prepared a polymer porous foam (HPSS) by a facile hydrothermal method. The HPSS presents a superhydrophilic wettability, an interpenetrating macroporous structure, and low thermal conductivity, which can well satisfy the criteria as an ideal candidate for photothermal materials. The HPSS/Fe3O4/PPy (polypyrrole) evaporator, of which a Fe3O4/PPy binary optical system served as a light absorption layer and HPSS was used as a porous substrate, was constructed through in situ growth of Fe3O4 particles followed by interfacial polymerization of PPy on the surface of HPSS. HPSS/Fe3O4/PPy shows an excellent light absorption capacity (92%) and photothermal conversion performance, with the solar energy conversion efficiency reaching up to 94.7% under 1 sun irradiation, which is much higher than that of HPSS/PPy (84.8%) composed of a unitary PPy light absorption layer. Interestingly, the presence of Fe3O4 particles could make directional migration in a magnetic field possible, thus facilitating its recovery as a self-floating solar generator in an open water area. Moreover, the HPSS/Fe3O4/PPy evaporator displays outstanding salt resistance properties and stability in various saline solutions, thus having great potential in practical desalination